2011
DOI: 10.3109/13880209.2011.576346
|View full text |Cite
|
Sign up to set email alerts
|

Ligusticum chuanxiongHort: A review of chemistry and pharmacology

Abstract: A large number of pharmacological and chemical studies during the last 10 years have demonstrated the vast medicinal potential of LC. It is still very clear that LC is a plant with widespread use now and also with extraordinary potential for the future. The documents strongly support the view that LC has beneficial therapeutic properties and indicates its potential as an effective adaptogenic herbal remedy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(106 citation statements)
references
References 53 publications
1
103
0
2
Order By: Relevance
“…6) Its effects are mainly related to its antioxidative, anti-apoptosis, and anti-inflammatory actions. 7) Recent studies have demonstrated that TMP can inhibit cell apoptosis under various conditions, such as hydrogen peroxide-induced oxidative damage in human umbilical vein endothelial cells 8) and in PC12 cells, 9) oxygen-glucose deprivation-induced neuronal apoptosis, 10) hypoxia-induced myocardial cell apoptosis, 11) and CoCl 2 -induced oxidative stress in PC12 cells. 12) These findings suggest that TMP pretreatment may enhance the survival of transplanted BMSCs and promote brain repair after stroke.…”
mentioning
confidence: 99%
“…6) Its effects are mainly related to its antioxidative, anti-apoptosis, and anti-inflammatory actions. 7) Recent studies have demonstrated that TMP can inhibit cell apoptosis under various conditions, such as hydrogen peroxide-induced oxidative damage in human umbilical vein endothelial cells 8) and in PC12 cells, 9) oxygen-glucose deprivation-induced neuronal apoptosis, 10) hypoxia-induced myocardial cell apoptosis, 11) and CoCl 2 -induced oxidative stress in PC12 cells. 12) These findings suggest that TMP pretreatment may enhance the survival of transplanted BMSCs and promote brain repair after stroke.…”
mentioning
confidence: 99%
“…For the assessment of cognitive recovery (i.e. Morris water maze (MWM) trial), deprivation of injection administration on the same day of the TBI procedure was specified as TMP (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) group (n=6) and vehicle (2-14) group (n=6). All procedures were approved by the Soochow University Animal Ethics Committee and conformed to the Guide for the Care and Use of Laboratory Animals.…”
Section: Experimental Animals and Drug Administrationmentioning
confidence: 99%
“…Additionally, compared with those of the vehicle group, the latency times in the hidden platform test were significantly decreased in the TMP group (P<0.05). When the injection administration on the same day as CCI procedure was not applied in the TMP and vehicle groups [TMP (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and vehicle (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)], a significant difference in latency time in the hidden platform test was not detected. Furthermore, in the spatial probe trial, on PID21 after CCI injury (~2 h after the fifth hidden platform trial), the TMP and vehicle groups demonstrated significantly worse performances than the sham group (P<0.05; Fig.…”
Section: Spatial Learning and Memory Following CCI Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…A Chinese herbal medicine, Ligusticum chuanxiong hort contains FA as one of the active ingredients and has been reported to possess a wide range of pharmacological properties (Ran et al 2011). It is clinically used to treat angina pectoris and hypertensive diseases in China.…”
Section: Introductionmentioning
confidence: 99%